Effect of Plant Revitalization Hormone and Foliar Fertilization on Growth and Yield of Boro Rice - Karim, MR; Rashid, MM; Salam, MA; Mazid, MA; Momin, MA; Islam, MS (Bangladesh Rice Journal, 2015)
Correction: In the last line of the abstract, the word 'increase' was replaced with the word 'reduced' on 25th November 2015. The correct sentence now reads "The application of PRH, Calsol and Magic Growth significantly reduced rice yield than that obtained with recommended fertilizer dose." Abstract Inherent soil fertility and application of exogenous fertilizer generally affect rice yield. Fertilization would be soil fertilization or foliar feeding through leaf area. Plant growth promoting substances also improve plant performance through modulation of its growth and yield. The study was conducted at BRAC Agricultural Research and Development Center (BARDC), Gazipur. The aim of the study was to find out the growth and yield of Boro rice as influenced by plant revitalization hormone (PRH) and liquid fertilizer Calsol and Magic Growth during dry season 2012-13 using randomized complete block design with three replications. Treatment consists of; T1=Recommend fertilizer dose of NPKS and Zn (Control), T2=T1+ recommended PRH, T3=T2 + half of the PRH, T4=Half of doses of T1 + PRH, T5=PRH, T6=Recommended fertilizer dose of NPK with three N top dressed along with Calsol, T7=Recommended fertilizer dose of NPK with 1st and 3rd split of N application and along with three split of Calsol application, T8=Recommended dose of liquid fertilizer Magic Growth. The effect of different treatment combinations of PRH and liquid fertilizer Calsol and Magic Growth showed significant difference (p<0.05) in panicle m-2, unfilled grain panicle-1, total grain panicle-1, and grain yield. However, none of the treatments out yielded the existing fertilizer application method. The application of PRH, Calsol and Magic Growth significantly reduced (corrected on 25th Nov. 2015) rice yield than that obtained with recommended fertilizer dose. Bangladesh Rice j. 2015, 19(1): 33-39